2018
DOI: 10.2169/internalmedicine.0663-17
|View full text |Cite
|
Sign up to set email alerts
|

The Surge in the Number of Circulating Tumor Cells Following Treatment with Sunitinib for Metastatic Renal Cell Carcinoma

Abstract: Circulating tumor cells (CTCs) are a promising biomarker for several cancers. We streamlined the experimental procedure of CTC immunofluorescent staining. We encountered a 72-year-old woman with metastatic right renal cell carcinoma (RCC) (clinical stage: T4N0M1), whose CTC number rapidly increased after the administration of sunitinib and then gradually decreased. The change in the CTC number appeared to coincide with laboratory data and hypertension, suggesting that a CTC analysis may be useful for promptly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…They concluded that the recurrence or metastasis of RCC was probably related to the variation trend of CTCs. Recently, Nagaya et al described a metastatic RCC patient, whose CTC counts rapidly increased after sunitinib treatment and then gradually decreased [ 39 ]. This result suggested that CTCs, as a promising biomarker, may be helpful for promptly monitoring the treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the recurrence or metastasis of RCC was probably related to the variation trend of CTCs. Recently, Nagaya et al described a metastatic RCC patient, whose CTC counts rapidly increased after sunitinib treatment and then gradually decreased [ 39 ]. This result suggested that CTCs, as a promising biomarker, may be helpful for promptly monitoring the treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a recent case report describing the use of an EpCAM-based microfluidic isolation of circulating epithelial cells by CytoQuest CR (Abnova, Taipei, Taiwan) and cytokeratin positivity, as a marker for CTC detection, managed to correlate CTC kinetics with response to sunitinib treatment of a metastatic RCC patient over a period of 20 days [ 25 ]. Although, said correlation emerged solely from the observation that, while CTC numbers dropped below baseline count at Day 20, CTscan examination on Day 128 showed a 14% reduction in the size of the primary renal lesion with concomitant shrinkage of the lung metastasis.…”
Section: Ctc Collection/detection In Renal Cell Carcinomamentioning
confidence: 99%
“…Indeed, circulating epithelial cell numbers have been shown to correlate with inflammation status in benign colon diseases [ 54 ] while circulating endothelial cells, which can also express cytokeratins, are known to correlate with pulmonary hypertension [ 60 ]. Therefore, the study by Nagaya et al raises further issues concerning the specificity of cytokeratin-based CTC counting, especially since their case report did not include any healthy controls [ 25 ].…”
Section: Ctc Collection/detection In Renal Cell Carcinomamentioning
confidence: 99%
“…Therefore, other methods of CTC detection are being explored for renal cancer . It is interesting to note that despite these detection‐related limitations, the clinical usefulness of CTCs in kidney cancer has been noted, such as the observation of a surge of CTCs after treatment with sunitinib, which is taken as an indication of treatment efficacy …”
Section: Introductionmentioning
confidence: 99%